Vascular medicine in older adults – A call for structured cooperation to improve care - Gerald Kolb; Farzin Adili; Michael Denkinger; Gesine Dörr; Ursula Müller-Werdan; Oliver J. Müller; Christoph Ploenes; Alexander Oberhuber; Barbara Rantner; Markus Steinbauer; Norbert Weiss; Rainer Wirth; et al. (Vasa, 2026)
Summary: The patient population treated by vascular medicine is becoming older, which goes along with an increasing number of patients presenting with frailty syndrome. The level of frailty determines the outcomes after vascular surgery or interventions. This position paper written by the German Society for Vascular Surgery and Vascular Medicine, the German Society for Geriatrics, and the German Society for Angiology – Society for Vascular Medicine summarizes the current evidence on the impact of frailty on the outcome after treatment for vascular diseases, and calls for a closer collaboration between geriatrics and vascular medicine and an integration of geriatric assessment in the preoperative or preinterventional evaluation of patients. Concrete and practical demands and tasks are formulated aiming at increasing awareness of geriatrization of the patient population, promoting research on the impact of frailty on the treatment of vascular patients and improving patients’ safety, reducing complications and enhancing quality of care of older vascular patients.